Efektivitas Program Latihan Interval Tinggi (Hiit) Terhadap Peningkatan Kebugaran Kardiorespirasi Pada Mahasiswa PKO UPRI - Wahyu Rahmatullah (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This research investigates the effectiveness of high-intensity interval training (HIIT) on enhancing cardiorespiratory fitness among students in the Sports Coaching Department at the University of the Republic Fighters of Indonesia. An experimental design with a pretest- posttest control group was employed, involving 20 students divided into an experimental group undergoing HIIT and a control group performing conventional training. The Multistage Fitness Test was used to measure VO₂max as an indicator of cardiorespiratory fitness. The HIIT program lasted six weeks, with sessions conducted three times weekly. Data analysis utilized paired t-tests for pretest and posttest comparisons within groups and independent t-tests for between-group comparisons at a significance level of 0.05. Results revealed a significant increase in VO₂max for the experimental group from 42.61 to 48.73 ml/kg/min (p=0.001), compared to an increase from 43.05 to 44.89 ml/kg/min for the control group (p=0.047). The study concludes that HIIT is effective in improving cardiorespiratory fitness among students.